Beyoncé’s style in Lemonade: a corpus-based analysis - Sidoruk (UFRGS), Natasha Barth; Rebechi (UFRGS), Rozane Rodrigues (ANTARES: Letras e Humanidades, 2020)
This study investigates the style in Beyoncé’s album Lemonade (2016) by comparing it to other artists’ works released simultaneously and to Beyoncé’s previous albums, in order to identify its distinctive semantic fields. AntConc is used to retrieve keywords. Recurring keywords are then analyzed in their contexts and eleven semantic fields are identified and discussed. The findings are compared to Lemonade’s critics’ reviews to reveal similarities and differences between their comments and this analysis, which takes quantitative data into consideration. The analysis confirms some of the features identified by the critics and provides a deeper insight into topics unnoticed by them.